Knowledge and Perception of the Ill Effects of Cosmetics Among Late Adolescent Girls - Ruby V.P.; Liya M. Alias; Prabisha. E.; Priya Prakash; Ragin Mariya; Rinta Sebastian; Riya Sebastian; Rosmol K. Joy; Sandra Sabu (International Journal of Women's Health Nursing And Practices, 2023)
The current research focused on examining the knowledge and attitude towards the negative effects of cosmetics among late adolescent girls studying at DM WIMS Pharmacy College in Meppadi, Wayanad. The study aimed to evaluate the level of knowledge and attitude toward the harmful effects of cosmetics among these girls and explore any potential associations between their knowledge, attitude and selected socio-demographic variables. To conduct the study, a quantitative approach using a descriptive method was adopted. The research took place at DM WIMS Pharmacy College in Meppadi, Wayanad. Convenient sampling was employed to select a sample size of 120 participants. A structured questionnaire was utilized to assess the knowledge level, while a checklist was employed to evaluate the attitude of late adolescent girls towards the negative effects of cosmetics. Out of 120 late adolescent girls the majority (64.1%) of them have average knowledge, (25%) of the sample has good knowledge, (10.8%) of the sample is having poor knowledge and no one is in an excellent category. The majority of the samples (82.5%) are having an unfavorable attitude, (17.5%) of the sample is having a moderately favorable attitude and no one is having a favorable attitude towards the ill effects of cosmetics. The results of the study revealed that there was no meaningful link between the participants' knowledge level and their socio-demographic characteristics. Similarly, no significant relationship was found between the participants' attitude level and their socio-demographic variables. The participants' knowledge scores ranged from 3 to 15, with an average score of 8.7 and a standard deviation of 3.75. Similarly, their attitude scores ranged from 24 to 36, with an average score of 29.9 and a standard deviation of 3.74. Overall, the study concluded that the late adolescent girls possessed an average level of knowledge regarding the ill effects of cosmetics, and their attitudes toward this topic were generally unfavorable. Therefore, there is a need to provide formal education to late adolescent girls, using appropriate channels, to raise awareness about the potential risks associated with cosmetics.
Keywords: Knowledge; attitude; ill effects of cosmetics; late adolescents